Investigations of the inhibition of copper corrosion in nitric acid solutions - G. Karthik; M. Sundaravadivelu (Egyptian Journal of Petroleum)
The influence of levetiracetam (LV) on the inhibition of copper corrosion in 0.5 M HNO3 solutions was studied using electrochemical techniques (potentiodynamic polarization and electrochemical impedance spectroscopy), weight loss as well as thermodynamic calculations to explore the adsorption mechanism of LV. The inhibition efficiency (IE%) was found to increase with increasing the concentration of the inhibitor and with decreasing the temperature. The maximum inhibition efficiency of 94.99% was observed in the presence of 300 ppm LV. The inhibition action of the compound LV was explained in terms of adsorption on the copper surface. The adsorption process follows Langmuir isotherm. Kinetic as well as thermodynamic parameters (activation energy, enthalpy of activation, entropy of activation and free energy of adsorption) were calculated and discussed. Electrochemical impedance spectroscopic technique (EIS) exhibit one capacitive loop indicating that, the corrosion reaction is controlled by the charge transfer process. Polarization measurements showed that the inhibitor is of mixed type. DFT calculations of LV were also studied to determine interactions with the copper surface. Further, the surface analysis via scanning electron microscope (SEM) and atomic force microscope (AFM) shows a significant improvement on the surface morphology of the copper plate. Results obtained from the different methods are in good agreement. The investigation revealed the possible application of LV drug as an environmentally friendly inhibitor for corrosion prevention under specific conditions.